Effects of face masks on fairness in on-site personnel selection during a pandemic - Zinn, Frank; Mittelstädt, Justin Maximilian (Frontiers in Psychology, 2023)
Despite significant challenges, personnel selection procedures had to continue as on-site testing in the Covid-19 pandemic. Health and safety measures and specifically the use of face masks threaten to limit the fairness of cognitive testing and behavioral observation in the assessment center. In this study, we compare the performance and pass rates of pilot selection under three different conditions in the selection campaigns of 2019 (pre-pandemic), 2020 (health and safety measures without mask), and 2021 (health and safety measures with mask). Mask wearing and other health and safety measures had no influence on the objective parameters of pilot selection. However, for some of the areas of competence in the assessment center subjective observability was rated lower for the condition with face masks. We conclude that the fairness and precision of selection processes are not compromised by wearing face masks and that a high degree of standardization in diagnostic instruments prevents a partially reduced subjective observability from affecting the selection’s outcome.